Alterations of Oxidative Phosphorylation Complexes in Papillary Thyroid Carcinoma - Franz A. Zimmermann; Daniel Neureiter; Wolfgang Sperl; Johannes A. Mayr; Barbara Kofler (Cells, 2018)
The papillary thyroid carcinoma (PTC) is the most common malignant tumor of the thyroid gland, with disruptive mutations in mitochondrial complex I subunits reported at very low frequency. Furthermore, metabolic diversity of PTC has been postulated owing to variable messenger RNA (mRNA) expression of genes encoding subunits of the oxidative phosphorylation (OXHPOS) complexes. The aim of the present study was to evaluate the metabolic diversity of the OXPHOS system at the protein level by using immunohistochemical staining. Analysis of 18 human PTCs revealed elevated mitochondrial biogenesis but significantly lower levels of OXPHOS complex I in the tumor tissue (p < 0.0001) compared to the adjacent normal tissue. In contrast, OXPHOS complexes II–V were increased in the majority of PTCs. In three PTCs, we found pathologic mutations within mitochondrially encoded complex I subunits. Our data indicate that PTCs are characterized by an oncocytic metabolic signature that is in low complex I is combined with elevated mitochondrial mass and high complex II–V levels, which might be an important factor for tumor formation.